THEORETICAL AND LEGAL ASPECTS OF POLYMERS IN FOREIGN ECONOMIC ACTIVITIES (Scientific journal of the Fergana State University, 2024)
This article describes the history of the creation of polymers, their structure, types and stages of production. The termsmonomer and polymer and their meaning are explained. The regulatory and legal analysis of the legislative base of the Republicof Uzbekistan on polymer materials has been carried out. The content and essence of the international Basel and StockholmConventions, as well as the scope of application, are shown. The grounds of the relevant regulatory documents for the benefitsand restrictions provided for the import and export of polymers in foreign economic activity are shown. Such processes asidentification of types of polymer products in foreign economic activity, exemption from customs duties, provision of guaranteesand compensations, restrictions on polyethylene terephthalate (PET) waste, fragments and waste, application of excise tax onpolyethylene granules and handling of polymer waste are highlighted.